Customer Satisfaction Evaluation Methods for Measuring and Implementing Service Quality - Grigoroudis, Evangelos; Siskos, Yannis; SpringerLink (Online service) (Boston, MA : Springer US, 2010)
This important new work provides a comprehensive discussion of the customer satisfaction evaluation problem by presenting an overview of the existing methodologies as well as the development and implementation of an original multicriteria method dubbed MUSA (MUlticriteria Satisfaction Analysis). The chief objective of MUSA is the development of a model able to evaluate the level of customer satisfaction both globally and partially for each of the characteristics or attributes of the product or service being considered. Furthermore, the method aims at providing an integrated set of results capable of analyzing customer needs and expectations and to justify their satisfaction level. And finally, the book examines the development of a decision support tool to help understand and apply results. Individual chapters consider the customer satisfaction problem, presenting the various quantitative and related consumer behavioral models; quality-based approaches; the MUSA method and its extensions and advanced topics; customer satisfaction surveys and barometers; applications of the MUSA method in real-world customer satisfaction surveys; and different information technology approaches related to customer satisfaction. Customer Satisfaction Evaluation: Methods for Measuring and Implementing Service Quality is intended for researchers and practitioners in marketing, quality management, service management, and anyone interested in applications of Multicriteria Decision Analysis (MCDA).
Basic Methodological Approaches -- Other Methodological Approaches -- MUSA: Multicriteria Satisfaction Analysis -- Extensions of the MUSA Method -- Advanced Topics on the MUSA Method -- Customer Satisfaction Surveys and Barometers -- Applications in Business Organizations -- Customer Satisfaction and Information Systems.
Keywords: Economics; Operations research; Economics/Management Science; Business/Management Science, general; Operations Research/Decision Theory; Operations Research, Mathematical Programming